Design and Development of Automatic Chip Feeder for Portable Smoker - Muhammad Ammar Bin Baharin; Muhamad Asri Bin Azizul; Muhammad Farid Bin Shaari (Progress in Engineering Application and Technology, 2021)
Portable smoker is an equipment used to cook meat by using only the heat release from the smoke. The source of heat that are used to cook the meat are the woods that are burnt inside the smoker chamber. However, there is a problem detected when smoker chamber need to always be checked and refilled to make sure the meat is cooked evenly from the smoke releases from the burning wood.  Hence, this study intends to fabricate and analyse an automated chip feeder for the smoker to feed the woods from the wood storage to the smoker chamber with less of human supervision by using a screw feeder shaft. The screw feeder shaft transfers the woods from the storage to the smoker chamber with help of a power window motor that rotates the screw feeder shaft. This study discovered that the screw feeder shaft can fed 119.4mm3 of woods for 1 second and 597mm3 of woods in the next 5 seconds. The volume of woods transferring rate from the wood storage to the smoker chamber is gradually constant to the time taken with the speed of 94 RPM. However, the RPM of the screw feeder shaft is the same eventhough the value of current changes because of the motor has reached its maximum torque. Moreover, the stall torque for the screw feeder to rotates when it is at rest is 2.9678x10-5Nm until the screw feeder starts to rotate because the stall torque is the torque that is produced by a mechanical device whose output rotational speed is zero. Therefore, the automated chip feeder for portable smoker is made to saves time and energy to manually feed the woods inside the smoker chamber with less of human supervision.